Allelic imbalance and microsatellite instability of the DCC gene in colorectal cancer in patients under the age of 35 using fluorescent DNA technology. Issue 1 (February 1998) - Chetty, R; Naidoo, R; Schneider, J
Abstract : AIM: To assess allelic imbalance and microsatellite instability in the region of the "deleted in colorectal cancer" (DCC) gene on chromosome 18q using fluorescent DNA technology in colorectal cancer in patients under the age of 35. METHODS: Thirty two cases of colorectal cancer in patients under the age of 35 and with no family history of colon cancer were retrieved. DNA was extracted by standard methods, polymerase chain reaction (PCR) was performed using Cy5 labelled primers to microsatellite markers (D18S21, D18S34, and D18S58) in the DCC gene. The results were analysed using software attached to an automated DNA sequencer. RESULTS: The patients ranged in age from 17 to 35 years. Nineteen were women, all had left sided tumours (tumours distal to the splenic flexure). Twenty eight cases were either stage C or D (using the Astler Coller system). The informativity of the three markers were as follows: D18S21, 25 of 32 (78.1%); D18S34, 18 of 32 (56.25%); D18S58, 24 of 32 (75%). Allelic imbalance for the markers, after excluding homozygous and microsatellite instability cases, was: D18S21, 31.8%; D18S34, 11.7%; and D18S58, 0%. Nine cases showed allelic imbalance for both D18S21 and D18S34, yielding a combined allelic imbalance frequency of 39.1%. Ten cases showed microsatellite instability in at least one marker, with microsatellite instability seen most commonly for D18S58. Three cases showed microsatellite instability for all three markers. CONCLUSIONS: Approximately 39% of cases showed allelic imbalance for D18S21 and D18S34 markers, while microsatellite instability was found in 31.25% of cases. This figure is higher than that encountered in sporadic colorectal cancer over the age of 50, suggesting a role for the DNA repair genes in the pathogenesis of these cancers occurring under the age of 35.